Building Bridges: The Role of an Undergraduate Mentor. Issue 1 (2nd January 2017) - Ward, Mark Daniel
ABSTRACT: I share some advice and lessons that I have learned from working with many wonderful students and colleagues, in my role as Undergraduate Chair of Statistics at Purdue University since 2008. I also reflect on developing, implementing, and sustaining a new living, learning community environment for statistics students.